Antibiotic‐Associated Disruption of Microbiota Composition and Function in Cirrhosis Is Restored by Fecal Transplant. Issue 4 (20th September 2018) - Bajaj, Jasmohan S.; Kakiyama, Genta; Savidge, Tor; Takei, Hajime; Kassam, Zain A.; Fagan, Andrew; Gavis, Edith A.; Pandak, William M.; Nittono, Hiroshi; Hylemon, Phillip B.; Boonma, Prapaporn; Haag, Anthony; et al.
Abstract : Patients with cirrhosis are often exposed to antibiotics that can lead to resistance and fungal overgrowth. The role of fecal microbial transplant (FMT) in restoring gut microbial function is unclear in cirrhosis. In a Food and Drug Administration–monitored phase 1 clinical safety trial, patients with decompensated cirrhosis on standard therapies (lactulose and rifaximin) were randomized to standard‐of‐care (SOC, no antibiotics/FMT) or 5 days of broad‐spectrum antibiotics followed by FMT from a donor enriched in Lachnospiraceae and Ruminococcaceae. Microbial composition (diversity, family‐level relative abundances), function (fecal bile acid [BA] deconjugation, 7α‐dehydroxylation, short‐chain fatty acids [SCFAs]), and correlations between Lachnospiraceae, Ruminococcaceae, and clinical variables were analyzed at baseline, postantibiotics, and 15 days post‐FMT. FMT was well tolerated. Postantibiotics, there was a reduced microbial diversity and autochthonous taxa relative abundance. This was associated with an altered fecal SCFA and BA profile. Correlation linkage changes from beneficial at baseline to negative after antibiotics. All of these parameters became statistically similar post‐FMT to baseline levels. No changes were seen in the SOC group. Conclusion: In patients with advanced cirrhosis on lactulose and rifaximin, FMT restored antibiotic‐associated disruption in microbial diversity and function. (Hepatology 2018; 00:000‐000).